Burnout Syndrome prevalence of on-call surgeons in a trauma reference hospital and its correlation with weekly workload: cross-sectional study - NOVAIS,RODRIGO NOBRE DE (2016)
ABSTRACT Objective: to determine the prevalence of Burnout Syndrome (BS) for surgeons working in referral hospital for trauma in Maceio and to evaluate the possible correlation between BS and weekly workload. Methods: cross-sectional study with 43 on-call surgeons at Professor Osvaldo Brandão Vilela General State Hospital, Maceió, between July and December, 2015. A self-administered form was used to evaluate BS through the Maslach Burnout Inventory (MBI) and socio-demographic characteristics among participants. Spearman's S test was used to compare BS and weekly workload. Significant level was 5%. Results: among the surgeons studied, 95.35% were male and the mean age was 43.9 ± 8.95 years. The mean weekly workload on call in trauma was 33.90 ± 16.82 hours. The frequency of high scores in at least one of the three dimensions of MBI was 46.5%. Professional achievement was correlated with weekly workload (P = 0.020). Conclusion: the prevalence of Burnout Syndrome among on-call surgeons in referral hospital for trauma was 46.5%. In this sample there was correlation between weekly workload and the Burnout Syndrome.